Mapping Spatial Distribution of Ammonia Nitrogen and Biochemical Oxygen Demand Along a New Road Construction Area - Kamaruzaman, Nur Wardiah; Khamidun, Mohd Hairul (Recent Trends in Civil Engineering and Built Environment, 2021)
It is a fact that construction activities cause water quality problems. The word most commonly applies to oceans, rivers, and streams, but contains smaller bodies of water, such as ponds, wetlands, or more rarely, puddles. The secondary data were used in this study to analyse the water quality index and develop spatial distribution mapping of NH3-N and BOD on new road construction areas by using software (Surfer 8.0). A total of seven sampling stations including WQ1 upstream and downstream stations were taken from previous project data in Sri Gading. The water quality in the stormwater varied spatially and focused parameters were NH3-N and BOD. The results revealed that the highest concentration of NH3-N was 2.2 mg/L at the WQ1 downstream station and while the lowest concentration was 0.1 mg/L was recorded at WQ2, WQ3 and WQ5 station. The highest concentration of BOD was 24.0 mg/L at WQ6 station, while the lowest concentrations were 2.0 mg/L at WQ2, WQ3 and WQ6 station. These concentrations exceeded the permissible limits of class II of the National Quality Water Standard. The pattern of the spatial distribution of NH3-N and BOD concentration show higher density color at the upper and lower part of the stormwater because the location was near to the plantation and residential area. The findings also revealed the importance of assessment of mapping spatial distribution water quality for better insight on surface water.